Boardwalk empire, The complete first season - Pitt, Michael 1981- (Warner Bros Entertainment Australia Ltd., 2012)
A lavish period drama set in Atlantic City, following the life and times of Nucky Thompson - the undisputed political and criminal mastermind whose grip on power and control of the city's liquor supply is under constant threat